2016
DOI: 10.4067/s0718-221x2016005000052
|View full text |Cite
|
Sign up to set email alerts
|

Decay resistance, thermal degradation, tensile and flexural properties of sisal carbon hybrid composites

Abstract: Sisal-carbon hybrid composites were produced from mixtures having different weight ratios of sisal, carbon fibers and recycled polypropylene. All formulations were tested and evaluated for tensile and flexural properties. In addition, the thermal stability of the sisal-carbon hybrid composites were examined via thermogravimetric analysis and decay tests were conducted to determine the degradation of the hybrid composites. Results showed that the biological durability and mechanical and thermal properties impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In the case of the composites, it is recognized that biological degradation is influenced, mainly by the resin and interfacial treatment, and the loss of interfacial strength can greatly influence the entire composite to biological degradation [148]. Very few studies were reported on the biological durability of the hybrid composite materials [109,[148][149][150]. The presence of carbon fiber was reported to reduce the decay rate of the hybrid composite in [149].…”
Section: Biological Durabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the composites, it is recognized that biological degradation is influenced, mainly by the resin and interfacial treatment, and the loss of interfacial strength can greatly influence the entire composite to biological degradation [148]. Very few studies were reported on the biological durability of the hybrid composite materials [109,[148][149][150]. The presence of carbon fiber was reported to reduce the decay rate of the hybrid composite in [149].…”
Section: Biological Durabilitymentioning
confidence: 99%
“…Very few studies were reported on the biological durability of the hybrid composite materials [109,[148][149][150]. The presence of carbon fiber was reported to reduce the decay rate of the hybrid composite in [149]. It was found that without carbon fibers, the composites exhibited the mass loss rate of 29.35 and 40.99% after exposure for six weeks to white rot (Trametes versicolor) and brown rot (Coniophora puteana) fungi, respectively.…”
Section: Biological Durabilitymentioning
confidence: 99%
“…Tufan et al [111] (2016) conducted decay tests to European standard EN 113 [112] fibre in the hybrid composite. After 16 weeks exposure, the mass loss rate was very limited (<7% for white rot and <5% for brown rot) in the hybrid composites.…”
Section: Compositesmentioning
confidence: 99%
“…In recent years, global researchers have increased their attention on using castoff synthetic fiber resources, including glass, carbon, aramid, and other types of polymer fibers, due to their incline in the ecological risk of pollution and removal of waste at the end of life. Surplus synthetic fibers are richly available from diversified sources, including polymer fibers, glass, fabric clippings in composites, and textile industry waste [11]. Hybrid polymer matrix composites (HPMCs) are extensively utilized in delicate body shells, ballistic helmets, and several other ballistic applications [12][13][14].…”
Section: Introductionmentioning
confidence: 99%